2010
DOI: 10.1111/j.1574-6968.2010.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate proteins for the diagnosis of Bartonella henselae infections using an immunoproteomic approach

Abstract: Bartonella henselae is an emerging gram-negative facultative intracellular pathogen transmitted via Ctenocephalides felis (cat fleas) or cat scratches. Bartonellosis is present mainly in the form of cat scratch disease (CSD), bacillary angiomatosis and infective endocarditis (IE). The methods used to diagnose B. henselae rely on culturing, immunofluorescent assays and molecular techniques. The objective of the present study was to identify candidate proteins for the serodiagnosis of bartonellosis with the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…We failed to detect HbpB in B. henselae using the western blot method. This result is in good agreement with those of proteomic analysis of outer membrane fractions of B. henselae and B. quintana [51], [52], [53], [54], [55], [56], which showed that HbpB was not detectable using this method. Since HbpA is the most abundant Hbp in B. henselae [52], [51], we checked its level in B. henselae pNS2Trc and B. henselae pNS2Trc ::hbpA AS using mouse antibody directed against HbpB.…”
Section: Resultssupporting
confidence: 90%
“…We failed to detect HbpB in B. henselae using the western blot method. This result is in good agreement with those of proteomic analysis of outer membrane fractions of B. henselae and B. quintana [51], [52], [53], [54], [55], [56], which showed that HbpB was not detectable using this method. Since HbpA is the most abundant Hbp in B. henselae [52], [51], we checked its level in B. henselae pNS2Trc and B. henselae pNS2Trc ::hbpA AS using mouse antibody directed against HbpB.…”
Section: Resultssupporting
confidence: 90%
“…The proteins recognized in vitro by antibodies in this work probably have the same antigenic determinants that induce antibodies in vivo. This approach has frequently been used to identify immunogenic proteins and, consequently, new targets to diagnose several diseases [41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Although similar results have been achieved in cryptococcosis using murine [55] and koala models [56], this is the first report in human beings.…”
Section: Discussionmentioning
confidence: 87%
“…Unlike research towards clinical serodiagnostic tools including immunogenic proteins of B. henselae [230][231][232][233], and towards the development of feline vaccines [234][235][236][237], there has been no research towards the development of human vaccines preventing B. henselae infections. One possible obstacle in this research is the variable gene pool of B. henselae strains promoting antigenic variation and defining the specific immune response [238].…”
Section: Bartonella Henselae Adhesin Amentioning
confidence: 99%